Normative Contents Bases of the State Standard of Education in the Field of Physical Education in General Secondary Education System of Poland - Оleksandr Mozolev (Pedagogical Discourse, 2015)
In the article the author made an analysis of the normative content of the standard of training of specialists in the field of physical education in the general secondary education system of Poland. It was established that the basis of the state education standard defines a basic training program on discipline «physical education». She sets the standard of student achievement at each stage of learning and defines the minimum level of development of motor skills when leaving school, gymnasium, lyceum, and also provides the necessary level of development of physical qualities and abilities of pupils for future life in modern civilization. The program establishes the core competencies of students, which give the opportunity to assess their readiness for further training. The basic program consists of several parts and formulated as follows: aims of education; school assignments; the content of practical knowledge, skills, optimum level of development of motor qualities, personal belief in the values of physical culture; achievement (competence) of students on completion of each stage of education.It is established that the basic curriculum is the starting point for the development of individual educational programs for physical education. It determines the overall achievement of students, and requires a deeper explanation and clarification. On the basis of generalization found that each teacher selects learning materials, determines the logistics capacity of the school, takes into account the interests and aspirations of young people, the tradition, and on this basis formulates his (authorʼs) training program. Strategy a teacher should focus on didactic training, stimulation of the activities of students for independent physical perfection, harmonious physical development and health preservation.Recommended two levels of requirements for students: the main level and full level. At the first level, students must meet the requirements stipulated in the basic training program, on the second level can be reached more meaningful learning objectives that apply in the authorʼs study programme.